Production of Sports Demonstration Videos in English As A Project-Based Learning Product - Sianipar, Rimma; Sinaga, Andromeda Valentino (Jurnal Penelitian Inovatif, 2025)
This study aims to develop a project-based learning (PBL) model for English instruction in the Physical Education, Health, and Recreation Study Program, focusing on the production of sports demonstration videos in English. The urgency of this research lies in the need for innovative teaching methods that not only enhance communication skills in English but also develop students' ability to present sports materials professionally. Project-Based Learning was chosen as it effectively integrates cognitive aspects, practical skills, and technology into a holistic approach. This study employs a qualitative research method, where students participate in a series of processes, including planning, production, and video presentation. The findings indicate that PBL significantly improves students' English proficiency, particularly in technical sports communication, while also fostering their creativity in utilizing digital technology. Moreover, the use of video editing software contributes to enhancing the quality of sports material presentations. However, challenges such as time constraints and students' technical skills in video production remain obstacles that need to be addressed. This research contributes to the development of a learning model that integrates sports, language, and technology, while also opening opportunities for further research in practice-based language instruction across various disciplines.